Diagnostic Evaluation of Chronic Nasal Obstruction Based on Nasal Endoscopy and CT Scan Paranasal Sinus - Chavan, Aparna (Indian J Otolaryngol Head Neck Surg, 2018)
Evaluation of the accuracy of objective diagnostic modalities for nasal obstruction and their comparison to each other to reach the correct diagnosis with minimum cost and highest accuracy. This study was conducted in the Department of Otorhinolaryngology and Head Neck Surgery, Chirayu Medical College and Hospital, Bhopal from August 2016 to September 2017. A total of 50 patients from age group 1–70 years irrespective of sex with complaints of chronic nasal obstruction, which were unresponsive to routine appropriate medical therapy, were selected for this study. Comparative study among findings of nasal endoscopy and CT scan of the paranasal sinuses done. After clinical examination, patients were subjected to high resolution computed tomography (HRCT) of paranasal sinuses and diagnostic nasal endoscopy (DNE). The diagnostic results of both modalities were compared. The most common symptoms were nasal obstruction and nasal discharge 100%, followed by post nasal drip 62%. The complaints related to eye and ears were less frequent, found in 4% only. CRS (Chronic Rhinosinusitis) was most common pathology of nose for nasal obstruction which is in 72% cases. Sinonasal polyp is present in 20% of cases. Inverted papilloma in 4% cases. Granulomatous disease (Rhinosporidiosis) in 2% cases. Malignancy in 2% cases. In this series of 50 cases, nasal endoscopy revealed various pathological abnormalities mainly in the osteomeatal area. These include mucopurulent discharge in middle meatus seen in 100% of cases (50 patients). This could not be revealed in HRCT. Oedematous and polypoid infundibular mucosa/polyp in nasal cavity in 28% cases (14 patients) where it was not diagnosed in HRCT in three patients. Hence DNE proved superior to HRCT. Other abnormalities detected on nasal endoscopy were septal deviation 80% of cases (40 patients), inferior turbinate hypertrophy 66% of cases (33 patients), middle turbinate hypertrophy/concha bullosa in 48% of cases (24 patients). DNS was diagnosed in 42 patients in HRCT other causes of nasal obstruction such as Agar nasi cell is detected in 16% (8 patients), medialised uncinate process in 16% (8 patients), paradoxical MT in 30% cases were diagnosed more accurately in nasal endoscopy than HRCT. So nasal endoscopy proved better than CT scan. Nasal obstruction is the most common presenting complaint in day to day otolaryngology practice. Nobody would disagree with the role of CT scan and diagnostic nasal endoscopy in diagnosing the nasal and paranasal pathologies. But as a treating physician we are always concerned about early diagnosis and cost effectiveness. At the same time we also have to consider about patient waiting and work load. In this study we attempted to find out whether diagnostic nasal endoscopy can be better then CT scan, so that we can treat our patient appropriately. Though there has been an increased demand for imaging the paranasal sinuses with coronal CT because of functional endoscopic sinus surgery, nasal endoscopy is a better option in diagnosing and assessing the extent of disease and anatomy.